1999
DOI: 10.1515/hf.1999.064
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resin Pockets in Seedlings of Pinus sylvestris L. by Mechanical Bending Stress during Growth

Abstract: Mechanical bending stress due to wind exposure has been suggested to be of major importance for induction of resin pockets in gymnosperm trees. In this study, this idea was tested experimentally by applying bending stress to 1-year-old internodes of five-year-old Pinus sylvestris L. seedlings during dormancy and/or growth. The stems were bent manually to 30° from their original upright position at regular intervals. About 30 % of the stems that were bent during growth were wounded in the xylem, whereas no woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…To a degree this contradicts the results of Temnerud et al (1999), who obtained resin pockets from severe bending of saplings in a controlled experiment. However, these mechanical stimuli were different than that one caused by a storm.…”
Section: Revisiting the Storms Hypothesismentioning
confidence: 57%
See 2 more Smart Citations
“…To a degree this contradicts the results of Temnerud et al (1999), who obtained resin pockets from severe bending of saplings in a controlled experiment. However, these mechanical stimuli were different than that one caused by a storm.…”
Section: Revisiting the Storms Hypothesismentioning
confidence: 57%
“…Publications supporting the storms hypothesis were, among others, presented for Norway spruce by Holzmann (1998), Seifert et al (2002), Wernsdörfer et al (2002), and Herb and Becker (2006). Temnerud et al (1999) were able to add further experimental evidence in a bending experiment with Scotch pine (Pinus sylvetris L.) seedlings where they induced similar anatomical structures in consequence of the bending stress as found in resin pockets of adult trees.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Information obtained in this study regarding branches, will be used in another study. Temnerud et al (1999) and Seifert et al (2010), in accordance with Larson (1994), chose to define resin pockets as: "...an intercellular circumferentially elongated pocket in the xylem with resin and wound tissue, which is usually occluded the same year as it is formed." A resin pocket is considered as a defect in some wood products as it decreases the value of timber and veneer and there is a need to understand the occurrence and causes of formation better.…”
Section: Introductionmentioning
confidence: 99%
“…One known controlled experiment was performed by Temnerud et al (1999) who applied bending stresses to 5-year-old Scots pine (Pinus sylvestris L.) trees during dormancy and/or growth. They found that approximately 30% of the stems that were exposed to bending stresses during growth had xylem wounds, whereas those stems exposed during dormancy and non-exposed controls did not exhibit xylem wounds.…”
Section: Introductionmentioning
confidence: 99%